An experimental magneto-inductive sensing technique for categorization of magnetic and non-magnetic materials - Arshad, Atika; Khan, Sheroz; Alam, A. H. M. Zahirul; Tasnim, Rumana (2012)
This paper presents the categorization of magnetic and non-magnetic materials across a low frequency band through conducting a non-contact measurement of a passive resistive element for low frequency applications. Three different materials have been used as core for the coupled coils. The experimental results for the test circuit with inductive and resistive load separately are obtained under different core materials. The response of the inductive and resistive element under test leads to determine the suitable conditions required for the accurate evaluation of the materials under test (MUT). In this work, material characterization is carried out under low frequency range for two different loads. Moreover for each material under test, the load is kept constant until all three specimens were tested. The change in permeability of material establishes the change of the output voltage, which is done through changing position of the movable core.